1999
DOI: 10.3310/hta3190
|View full text |Cite
|
Sign up to set email alerts
|

What role for statins? A review and economic model.

Abstract: et al. What role for statins? A review and economic model. Health Technol Assess 1999;3(19). Health Technology Assessment is indexed in Index Medicus/MEDLINE and Excerpta Medica/ EMBASE. Copies of the Executive Summaries are available from the NCCHTA web site (see overleaf). NHS R&D HTA Programme T he overall aim of the NHS R&D Health Technology Assessment (HTA) programme is to ensure that high-quality research information on the costs, effectiveness and broader impact of health technologies is produced in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(30 citation statements)
references
References 76 publications
2
27
0
1
Order By: Relevance
“…Early trial evidence was limited to people aged under 70 years (Scandinavian Simvastatin Survival Study Group 1994) which may have been partly responsible for lower levels of prescribing in people over this age, as described in earlier studies (Robson 2008). However, more recent research in both the UK and elsewhere still shows that individuals over the age of 75 are prescribed 40Á90% less than younger age groups despite evidence that statin treatment can be beneficial in older patients (Ebrahim et al 1999, Reid et al 2002, Ward et al 2004, Hippisley-Cox et al 2005, Ramsay et al 2005, Gnavi et al 2007. Ecological studies have found that practices with a greater proportion of patients over the age of 75 tend to prescribe fewer statins (Ashworth et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Early trial evidence was limited to people aged under 70 years (Scandinavian Simvastatin Survival Study Group 1994) which may have been partly responsible for lower levels of prescribing in people over this age, as described in earlier studies (Robson 2008). However, more recent research in both the UK and elsewhere still shows that individuals over the age of 75 are prescribed 40Á90% less than younger age groups despite evidence that statin treatment can be beneficial in older patients (Ebrahim et al 1999, Reid et al 2002, Ward et al 2004, Hippisley-Cox et al 2005, Ramsay et al 2005, Gnavi et al 2007. Ecological studies have found that practices with a greater proportion of patients over the age of 75 tend to prescribe fewer statins (Ashworth et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several assumed that there would be no continued benefit after the trial end point or a coronary event [83,91,93,100]. Others assumed that treatment benefits would continue indefinitely [30,85,95,96,101]. One solution is to provide results on both possible extremes, as done by Tsevat et al [111].…”
Section: Discussion About Studies For Long Term Interventionsmentioning
confidence: 99%
“…The problem with using trial data is that it is not possible to generalise the results to different populations. Several models [85,95,96] assume that non-fatal events and health cost savings are proportional to the mortality benefit seen. Most studies measured the outcome of life years saved, rather than quality adjusted life years saved.…”
Section: Discussion About Studies For Long Term Interventionsmentioning
confidence: 99%
See 2 more Smart Citations